STATE, NEOLIBERALISM AND BUSINESS IN COSTA RICA: THE CAFTA CONJUNCTURE - Arias Chavarría, Esteban (2019)
This paper focuses on the relations between the business elite grouped in the main Costa  Rican business association and the state elite during the cafta political juncture, 2002-2007.  It employs the conjuncture analysis supported on documentary resources and testimonies of key witnesses. This was a social process that articulated significant sociopolitical tensions linked to the neoliberal accumulation strategy and the correlation between the interest of the business and the political elites, as well as their differences regarding the control of thesocial conflict in this period.